2018
DOI: 10.1021/acscatal.8b01432
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Confidence in DFT Predicted Surface Pourbaix Diagrams and Associated Reaction Pathways for Chlorine Evolution

Abstract: Catalytic activity predictions and the identification of active sites rely on precisely determining the dominant reaction mechanism. The activity governing mechanism and products could vary with the catalyst material, which can be described by material descriptor(s), typically the binding strength(s) of key intermediate species. Density functional theory calculations can be used to identify dominant reaction mechanisms. However, the dominant reaction mechanism is sensitive to choice of the exchange correlation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 61 publications
11
113
0
Order By: Relevance
“…Section 2) are scaled as function of the free formation energy of oxygen, Δ G 0 (O ot ) (cf. Figure ), which has been proven to serve as a descriptor for activity trends in the CER over transition metal oxide electrodes . I would like to emphasize that the discussed type of scaling differs from conventional linear scaling relationships in the literature: commonly, linear scaling relationships of an adsorbate as function of a descriptor are determined within a homologous series of materials .…”
Section: Linear Scaling Relationships Of the Limiting Ocl And Ooh Adsmentioning
confidence: 99%
“…Section 2) are scaled as function of the free formation energy of oxygen, Δ G 0 (O ot ) (cf. Figure ), which has been proven to serve as a descriptor for activity trends in the CER over transition metal oxide electrodes . I would like to emphasize that the discussed type of scaling differs from conventional linear scaling relationships in the literature: commonly, linear scaling relationships of an adsorbate as function of a descriptor are determined within a homologous series of materials .…”
Section: Linear Scaling Relationships Of the Limiting Ocl And Ooh Adsmentioning
confidence: 99%
“…However, it is questionable, whether Δ E O is a suitable choice to describe the selectivity problem of the competing CER and OER adequately. In case of the CER, the usage of Δ E O appears justified, since for transition‐metal oxides, such as RuO 2 and IrO 2 , it has been shown that oxygen atoms in junction with the underlying metal atom (Me) serve as active sites for electrochemical chlorine formation: the adsorption and discharge of a chloride anion from the electrolyte solution results in the formation of an OCl adsorbate, reconciled as precursor for the formation of gaseous chlorine (cf. equation ). trueMe-normalO+Cl-Me-OCl+normale-1.em0.166667em0.277778em(ΔGOCl) …”
Section: Introductionmentioning
confidence: 99%
“…The free energy diagram along the reaction coordinate (cf. Figure c) provides deep mechanistic insights into electrocatalytic processes, in this case the Volmer‐Heyrovsky mechanism, which has been confirmed for the CER over RuO 2 (110) by various experimental and theoretical studies . While for small overpotentials, that is, η CER <0.125 V, the Heyrovsky step is kinetically limiting according to the highest transition state free energy, the rate‐determining reaction step switches to the Volmer step if the applied overpotential exceeds 0.125 V. Since the change in the rate‐determining reaction step was quantified in the overpotential regime between 0.10 V and 0.15 V, the affiliated error bars for the determination of the threshold overpotential (0.125 V) may not exceed 25 mV if other error sources, such as the determination of the reversible equilibrium potential, are neglected.…”
Section: Resultsmentioning
confidence: 65%
“…As in case of prototypical activity‐based volcano plots, the construction of an activity‐stability volcano plot for the CER over RuO 2 (110) is based on linear scaling relationships for the involved active site O ot and the precursor OCl ot within the Volmer‐Heyrovsky mechanism (cf. Figure c) .…”
Section: Resultsmentioning
confidence: 99%